A comprehensive review on the implementation of technological Systems, Standards, and interfaces used in the food and agriculture industries. (2022) - Kassanuk, Thanwamas; Phasinam, Khongdet
Abstract: Information and communication technologies (ICTs) are crucial mediums for accessing and managing information in order to generate knowledge. ICT plays a critical role in adopting new and traditional technologies for information creation and coordination among extension workers. ICTs provide enormous potential in the agriculture sector to overcome restrictions such as low education levels, diverse cultures and subcultures, and a lack of motivation in technology usage, which is preventing the industry's further expansion. Information and communication technologies (ICT) constitute an essential medium for overcoming these challenges through cost-effective and creative technology, creating enormous potential in hitherto untapped sectors of the agricultural sector. Mobile phone technologies are regarded as the greatest medium for market expansion and communication potential in the agricultural industry. This article provides a comprehensive review on roll of ICT in improving the food and agriculture sector.